Light adaptation in letter contrast sensitivity: The influence of optical and neural mechanisms - Arranz, I. (2013)
This work discusses the level of implication of the optical and physiological mechanisms in letter contrast sensitivity (CS) under different conditions of environmental lighting. A study was carried out on 26 eyes with normal ocular health. Sixteen conditions of light, obtained by combining different test luminances (from 10 to 600 cd/m2) and surround luminances (from 1 to 600 cd/m2) were considered. The results reveal a significant influence of optical factors (pupil size variations and glare effects) on CS when surround luminance changes, and dominance of neural effects when test luminance changes. Furthermore, test size and illumination conditions are provided for which letter threshold contrasts are not sensitive to surround luminance changes.